2011
DOI: 10.1371/journal.pgen.1002336
|View full text |Cite
|
Sign up to set email alerts
|

HIF–VEGF Pathways Are Critical for Chronic Otitis Media in Junbo and Jeff Mouse Mutants

Abstract: Otitis media with effusion (OME) is the commonest cause of hearing loss in children, yet the underlying genetic pathways and mechanisms involved are incompletely understood. Ventilation of the middle ear with tympanostomy tubes is the commonest surgical procedure in children and the best treatment for chronic OME, but the mechanism by which they work remains uncertain. As hypoxia is a common feature of inflamed microenvironments, moderation of hypoxia may be a significant contributory mechanism. We have invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 85 publications
2
89
2
Order By: Relevance
“…Additionally, IQGAP1 was found to be needed to organize ROS-dependent VEGF signaling via VEGFR2 in endothelial cells which may contribute to the repair and maintenance of blood vessels and angiogenesis (Yamaoka-Tojo et al 2004). VEGF signaling is known to induce angiogenesis, increase vascular permeability, and influence inflammation in several ways, all which could increase risk of chronic otitis media by effusion build-up and in- Cheeseman et al 2011). These roles of IQGAP1 indicate that IQGAP1 may be involved in COME/ ROM pathogenesis though further investigation is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IQGAP1 was found to be needed to organize ROS-dependent VEGF signaling via VEGFR2 in endothelial cells which may contribute to the repair and maintenance of blood vessels and angiogenesis (Yamaoka-Tojo et al 2004). VEGF signaling is known to induce angiogenesis, increase vascular permeability, and influence inflammation in several ways, all which could increase risk of chronic otitis media by effusion build-up and in- Cheeseman et al 2011). These roles of IQGAP1 indicate that IQGAP1 may be involved in COME/ ROM pathogenesis though further investigation is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factor-1a (HIF-1a) is a transcription factor that activates the expression of a number of genes involved in diverse aspects of cellular and physiologic processes (33,34). Under hypoxic conditions, HIF-1a forms a heterodimer with HIF-1b, and binds to the hypoxia-responsive elements of the promoters to activate downstream hypoxia-responsive genes, including VEGF, to increase angiogenesis and tumor metastasis or to promote cancer cell proliferation and migration (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple factors involved in this process. It has been reported that anatomic abnormality, genetic predisposition, and middle ear immunity play important roles in the pathogenesis of COM [3][4][5][6][7]. To make middle ear infection chronic, there must be some compromised innate or adaptive immunity in the middle ear mucosa.…”
Section: Introductionmentioning
confidence: 99%